Improving the biocontrol potential of entomopathogenic nematodes against Mamestra brassicae: effect of spray application technique, adjuvants and an attractant. Issue 1 (29th May 2013) - Beck, Bert; Brusselman, Eva; Nuyttens, David; Moens, Maurice; Temmerman, Femke; Pollet, Sabien; Van Weyenberg, Stephanie; Spanoghe, Pieter
Abstract BACKGROUND Steinernema carpocapsae Weiser, an entomopathogenic nematode (EPN), is a potential biological control agent for the cabbage moth (Mamestra brassicae L.). This research aimed to identify a suitable spray application technique, and to determine whether yeast extract added to an EPN spray has an attracting and/or a feeding stimulant effect on M. brassicae. The biological control capabilities of EPN against this pest were examined in the field. RESULTS Good coverage of the underside of cauliflower leaves, the habitat of young instar larvae (L1–L4) of M. brassicae was obtained using different spray boom configurations with vertical extensions that carried underleaf spraying nozzles. One of the configurations was selected for field testing with an EPN spray. Brewer's yeast extract stimulated larval feeding on leaves, and increased the mortality of these larvae when exposed to EPN. The field trial showed that a spray application with S. carpocapsae, Addit and xanthan gum can effectively lower the numbers of cabbage heads damaged by M. brassicae. Brewer's yeast extract did not significantly increase this field performance of EPN. CONCLUSION Steinernema carpocapsae, applied with an appropriate spray technique, can be used within biological control schemes as part of a resistance management programme for Bt. © 2013 Society of Chemical Industry